The Effect of Wise Leadership on Sustainable Performance - rasheed, haneen; Kadhim Saeed, Hadeel (Journal of Economics and Administrative Sciences, 2025)
The research aims to know the impact of wise leadership in its dimensions (Intellectual shrewdness, Spurring action, Moral conduct, and Cultivating humility) in achieving sustainable performance (economic performance, social performance, and environmental performance). The researcher chose the Midland Oil Company as a field for applying the research. The researcher distributed a questionnaire to a purposive sample of (126) managers working within the Midland Oil Company, which included (department managers and division officials). The number of questionnaires valid for analysis was (121) out of (126) distributed questionnaires. The researcher relied on the questionnaire as a primary source for collecting information from the research sample. The researcher adopted the descriptive analytical method in collecting the data and information required by the research. The results concluded that there is a positive impact relationship between wise leadership and its dimensions in achieving sustainable performance and its dimensions. The research results also indicated that the top leadership in the Midland Oil Company seeks to enhance its sustainable performance and long-term success by preserving the environment, contributing to social responsibility, and achieving economic profits. The current research explains the role of leadership in the Midland Oil Company in supporting the economic, social, and environmental aspects of the state and society through adopting sustainable performance practices. Research Type: Research Paper.